2014
DOI: 10.4103/2156-7514.141560
|View full text |Cite
|
Sign up to set email alerts
|

Omental Nodular Deposits of Recurrent Chromophobe Renal Cell Carcinoma Seen on FDG-PET/CT

Abstract: We present the case of a 69-year-old male with chromophobe renal cell carcinoma (RCC). Chromophobe RCC accounts for only 4% of renal cancers and it is the least aggressive type. Omental nodular deposits due to RCC metastasis are very rare and it is reported only in more aggressive forms of RCC. This is the first report that shows FluoroDeoxyGlucose – Positron Emission Tomography/Computed Tomgraphy (FDG-PET/CT) images of omental nodular deposits from chromophobe RCC. FDG-PET/CT is becoming very useful in restag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…reported omental nodular deposits detected by F-18 FDG PET/CT scan in aggressive form of RCC. [ 7 ] Tatoglu et al . showed the usefulness of F-18 FDG PET/CT in detecting metastasis in the subcutaneous fatty tissue of the right thigh region and similarly Bhoil et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported omental nodular deposits detected by F-18 FDG PET/CT scan in aggressive form of RCC. [ 7 ] Tatoglu et al . showed the usefulness of F-18 FDG PET/CT in detecting metastasis in the subcutaneous fatty tissue of the right thigh region and similarly Bhoil et al .…”
Section: Discussionmentioning
confidence: 99%
“…Win et al reported omental nodular deposits detected by F-18 FDG PET/CT scan in aggressive form of RCC. [7] Tatoglu et al showed the usefulness of F-18 FDG PET/CT in detecting metastasis in the subcutaneous fatty tissue of the right thigh region and similarly Bhoil et al presented an isolated deltoid muscle metastasis 12 years after radical nephrectomy. [2,8] Tracheal metastasis from primary lung cancer is commonly seen, but very rare site of involvement from nonpulmonary malignancies with the prevalence of 2% found in autopsy studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, development of metachronous omental metastasis(es), particulary in the absence of diffuse peritoneal involvement, is an extremely rare condition in the natural history of RCC. Win et al have recently reported a patient with an initially T3N0M0 chromopobe RCC, who developed an interaortocaval lymph node enlargement 1 year after laparoscopic radical nephrectomy [9] . They have incidentally discovered an additional omental metastatic deposit while removing this interaortocaval mass.…”
Section: Discussionmentioning
confidence: 99%
“…They have incidentally discovered an additional omental metastatic deposit while removing this interaortocaval mass. Despite surgical excision and adjuvant therapy with tyrosine kinase inhibitors, the omental nodules recurred and they were able to detect this recurrence via FDG avidity on surveillance PET/CT studies [9] .…”
Section: Discussionmentioning
confidence: 99%